THE CONCEPT OF VIRTUAL THREAT AND ITS THEORETICAL STUDY - Mahammadiyev Jamol Rustam ogli (Bright Mind Publishing, 2025)
This article discusses the concept of virtual threats and their theoretical study. Virtual threats are dangers spread through the internet and information technologies in modern digital society, negatively affecting the spiritual-moral worldview and psychological state of youth. The article provides a detailed analysis of the types of virtual threats — informational, psychological, moral, and cybersecurity threats. It also examines the impact of virtual threats on the morality and ethical outlook of youth, as well as the scientific methods and modern approaches to their study. The article emphasizes the importance of implementing comprehensive measures to understand and counter virtual threats in contemporary society.
Keywords: Virtual threats, digital society, information security, cyber threats, psychological threats, moral threats, youth, spirituality, interdisciplinary approach, prevention.